Proteomic Studies to Understand the Mechanisms of Peach Tissue Degradation by Monilinia laxa - Rodríguez-Pires, Silvia; Melgarejo, Paloma; De Cal, Antonieta; Espeso, Eduardo A. (Frontiers in Plant Science, 2020)
Monilinia laxa is a necrotrophic plant pathogen able to infect and produce substantial losses on stone fruit. Three different isolates of M. laxa were characterized according to their aggressiveness on nectarines. M. laxa 8L isolate was the most aggressive on fruit, 33L isolate displayed intermediated virulence level, and 5L was classified as a weak aggressive isolate. Nectarine colonization process by the weak isolate 5L was strongly delayed. nLC-MS/MS proteomic studies using in vitro peach cultures provided data on exoproteomes of the three isolates at equivalent stages of brown rot colonization; 3 days for 8L and 33L, and 7 days for 5L. A total of 181 proteins were identified from 8L exoproteome and 289 proteins from 33L at 3 dpi, and 206 proteins were identified in 5L exoproteome at 7 dpi. Although an elevated number of proteins lacked a predicted function, the vast majority of proteins belong to OG group “metabolism”, composed of categories such as "carbohydrate transport and metabolism" in 5L, and "energy production and conversion" most represented in 8L and 33L. Among identified proteins, 157 that carried a signal peptide were further examined and classified. Carbohydrate-active enzymes and peptidases were the main groups revealing different protein alternatives with the same function among isolates. Our data suggested a subset of secreted proteins as possible markers of differential virulence in more aggressive isolates, MlPG1 MlPME3, NEP-like, or endoglucanase proteins. A core-exoproteome among isolates independently of their virulence but time-dependent was also described. This core included several well-known virulence factors involved in host-tissue factors like cutinase, pectin lyases and acid proteases. The secretion patterns supported the assumption that M. laxa deploys an extensive repertoire of proteins to facilitate the host infection and colonization and provided information for further characterization of M. laxa pathogenesis.